2016
DOI: 10.1038/srep35304
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal 2H-MoSe2 broad spectrum active photocatalyst for Cr(VI) reduction

Abstract: To make full use of the solar energy, exploring broad spectrum active photocatalysts has become one of the core issues for photocatalysis. Here we report a novel hexagonal 2H-MoSe2 photocatalyst with ultraviolet (UV)-visible-near infrared (NIR) light response for the first time. The results indicate that the MoSe2 displays excellent photo-absorption and photocatalytic activity in the reduction of Cr(VI) under UV and visible even NIR light irradiation. MoSe2 synthesized at pH value of 2 achieves the highest Cr(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…To evaluate the adsorption abilities of NICs adsorbents, batch adsorption experiments were performed using 250 mL conical flasks containing 100 mL of working solutions. The influence of operating parameters such as time (10-120 min), NICs amount (0.1-0.5 g), dye concentration (100-350 mg/L), and pH (3)(4)(5)(6)(7)(8)(9)(10)(11) on MG dye remediation was investigated in batch studies. Typically, 0.1 g of NICs and MG solution (100 mL) with the desired pH and concentration were added to a 250 mL conical flask and stirred continuously.…”
Section: Batch Adsorption Studiesmentioning
confidence: 99%
“…To evaluate the adsorption abilities of NICs adsorbents, batch adsorption experiments were performed using 250 mL conical flasks containing 100 mL of working solutions. The influence of operating parameters such as time (10-120 min), NICs amount (0.1-0.5 g), dye concentration (100-350 mg/L), and pH (3)(4)(5)(6)(7)(8)(9)(10)(11) on MG dye remediation was investigated in batch studies. Typically, 0.1 g of NICs and MG solution (100 mL) with the desired pH and concentration were added to a 250 mL conical flask and stirred continuously.…”
Section: Batch Adsorption Studiesmentioning
confidence: 99%
“…As the majority of water treatment facilities are located outdoors, the availability of solar energy can be useful for photocatalytic technology in water treatment. Chu et al [198] reported that the development of hexagonal 2H-MoSe 2 photocatalyst exhibits outstanding photo-absorption and photocatalytic reaction in reducing hexavalent chromium (Cr(VI)) under ultraviolet (UV) light. The 2H-MoSe 2 yields 99% Cr(VI) reduction rate with the presence of UV light.…”
Section: Photocatalyst Technology In Wastewater Treatmentmentioning
confidence: 99%
“… Catalysts Light source Light intensity (mW/cm 2 ) Catalyst concentration (g/L) Stirring Decolourization rate k (min -1 ) Recycling times Refs. C fiber@MoSe 2 NPCSC 5 W LED lamp 36 1 no 34.7% in 120 min 0.0034 3 [1] C quantum dots decorated MoSe 2 300 W Xe lamp λ ≥ 400 nm 741 1 yes 99% in 180 min 0.026 3 [9] Hexagonal 2H-MoSe 2 nanoparticles 300 W Xe lamp λ ≥ 400 nm 741 1 yes 94% in 180 min 0.027 3 [10] MoSe 2 nanosheets/TiO 2 nanoparticles composite 400 W metal halogen lamp λ ≥ 400 nm 1 yes 91% in 120 min 0.0141 [11] MoSe 2 nanoparticles 400 W metal halogen lamp λ ≥ 400 nm 1 yes 95% in 250 min 5 [12] 3D MoS 2 /r-GO aerogel 300 W Xe lamp 545 0.67 yes 92% in 120 min [13] 2D MoS 2 nanosheet coated Bi 2 S 3 discoids 300 W Xe lamp λ ≥ 400 nm 700 0.25 yes 97% in 30 min 3 [14] …”
Section: Datamentioning
confidence: 99%